Avaliação do Programa de Aquisição de Alimentos (PAA) e do Programa Nacional de Alimentação Escolar (PNAE) da agricultura familiar : estudo de caso na microrregião de Ubá-MG - Oliveira, Leandro Gomes de (2015)
The Food Acquisition Program (PAA) and the National Program of School Food (PNAE) are public policies designed to ensure improve food to two heterogeneous publics, the population who are in situations of food insecurity and students from public schools. These policies have as source of supply the family farming, an important segment responsible for producing much of the food destined to internal market. Nevertheless, it is necessary to understand the real impact of the PAA and PNAE on suppliers farmers and to know which of these policies have better impact on the development of family farming. There are studies in the literature addressing the impact assessment on the family farm in both the political and in different cities. However, rarely there are studies analyzing the real impact of policies, PAA e PNAE at the same city. From this, the present dissertation aims to evaluate the impact of social programs and PAA PNAE in economic and social conditions of the farmers in Uba city, Minas Gerais. This will be done using descriptive and multivariate statistical and statistical significance test seeking to achieve this goal. The results show that economic impact of the PAA and PNAE in beneficiary farmers were revenue and product quality. Despite this, weren`t find significant differences of these impacts between these policies. In social sphere, variable quality of life impacted positively only on PAA farmers. Thus, it can be said that the effects of public policies are similar and the PAA and PNAE can be treat as complementary policies.